COBRE on Opioid and Overdose: A Collaborative Research-Based Center Addressing the Crises in Rhode Island and Beyond - GREEN, TRACI C. (R I Med J (2013), 2021)
Overdose deaths across the country have spiked since the onset of the COVID-19 pandemic. It is crucial now, more than ever, to address the continuing and worsening, complex and dynamic opioid and overdose epidemics. In 2018, The Center of Biomedical Research Excellence (COBRE) on Opioids and Overdose, based at Rhode Island Hospital, launched with three major goals: 1) establish a center of scientific excellence on opioids and overdose; 2) train the next generation of scientists to become independent investigators and address the opioid and overdose crises; and 3) contribute to the scientific progress and solutions to combat these epidemics. To date, we have made substantial progress. While the opioid and overdose crises continue to evolve, the COBRE on Opioid and Overdose and its team of investigators are well poised to address the daunting task of understanding and meaningfully addressing these deadly epidemics, with the ultimate goal of saving lives.